ROLE OF CREDIT REFERENCE BUREAUS ON CREDIT ACCESS IN KENYA: A SURVEY OF COMMERCIAL BANKS IN KENYA - Gaitho, Nancy Wanjiru (European Scientific Journal, ESJ, 2013)
Inadequate access to credit, limits poor people from a fair share of resources in society, depriving them of basic needs and opportunities in life. Universally, commercial banks are facing problem of non-repayment of loans. This problem can be overcome through monitoring the behavior of borrowers. Thus, the idea of establishing Credit Reference Bureau (CRB) was conceived in order to assist banks in determining credit worthiness of their borrowers. CRBs allows for credit information sharing among the financial institutions. This study explores the effect of credit reference bureaus on credit access in Kenya. The sample of 96 respondents was drawn from the employees working in the headquarters of these banks targeting managers within the finance, strategy and business development portfolios/dockets in the 42 commercial banks in Kenya. The study found out that CRB reduces borrowing cost and loan delinquencies to a moderate extent. It further established that CRB has enhanced effective risk identification/monitoring and microcredit extension in Kenya. The study therefore recommends that lenders and CRB should work closely to ensure that there is no information asymmetry and therefore ensure that credit flows to deserving borrowers.